KERJASAMA INDONESIA DAN JERMAN DALAM PENGEMBANGAN ENERGI PANAS BUMI (GEOTHERMAL) 2010-2012 DI INDONESIA - Geby Giandwinuary; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research describes about the cooperation between Indonesia and German in renewable energy. Politically Germany Consistent support integrity and cooperation among regions of Indonesia and Indonesia welcomed efforts to resolve internal conflicts through negotiation. Even since 2010, Indonesia and Germany increased cooperation in energy field. Germany and Indonesia have conducted a number of joint projects in the renewable energy sector in recent years, including geothermal energy as one of the safeguards climate ,and to support national energy security.The method used in this study is a description which aims to systematically describe in this cooperation between Indonesia and Germany in the development of Geothermal Energy, based on techniques of data collection is library research, the data collection techniques to find the data from the literature books, information based review of the literature or whether sourced reference articles, magazines, newspapers, journals, bulletins, internet, and important notes on matters related to the issue being studied by the author. The theory used in this study is the theory interpendesi International cooperation.The results of this study are: Indonesia and Germany Cooperation in the development of geothermal energy in Indonesia in 2010 - 2012 have been performed optimally. It is seen that Germany has provided funding for geothermal energy development in Aceh. Germany's determination to move on to new and renewable energy grew stronger after the government made a policy Energiewende (German Energy Transition) in 2010.Keywords: Cooperation, Energy. Geothermal, Development, Indonesia, Jerman